SPORTS AND THE VALENCIES OF HUMAN RIGHTS PROTECTION (University Arena, 2025)
„Practicing sports is a human right”1, so „every person should be able to practice sports according to their needs". Although the European Convention on Human Rights does not officially recognize this right, the  European Court of Human Rights has emphasized, through its case law, the importance of respecting fundamental human rights in the field of sports. The decisions of the sports federations challenged before the courts or of the sports arbitration entities, have often serious consequences for the sports actors. That is why it is particularly important to analyze the guarantees granted from the point of view of human rights so that,  taking into account also the autonomy of the sports structures, national or international sports federations respect these rights and, at the same time, develop the most appropriate legal mechanisms and instruments.In this context, the respect for human rights, seen as universal principles, has become a key issue in sports disputes, both for sports organizations and for courts or sports arbitration entities.Objectives. In the present scientific approach we set out to identify the sources and mechanism of human rights in the field of sports.Methods. We will use the historical method, we will analyze the sources of human law, and, at the same time, the relevant jurisprudence of the European Court of Human Rights.Results. As issues in the field of sports are closely linked to non-respect for human rights, we aim to highlight their importance, so that there is a balance between the interests of the parties: the sports structures that draw up their own regulations and the actors of sport.Conclusion. Sports is closely linked to the protection of human rights because, on the one hand, „practicing sports is a fundamental right of everyone”, and on the other hand, this field, by its essence, implies the existence of fundamental principles. The knowledge of the sources and mechanisms of protection of human rights in the field of sports will allow sports structures to develop, in accordance with the principle of autonomy, policies of their own regulations, which will maintain an adequate balance of the interests of the parties.